Fabrication of vertically aligned Pd nanowire array in AAO template by electrodeposition using neutral electrolyte - Taşaltın, Nevin (Springer, 2010)
A vertically aligned Pd nanowire array was successfully fabricated on an Au/Ti substrate using an anodic aluminum oxide (AAO) template by a direct voltage electrodeposition method at room temperature using diluted neutral electrolyte. The fabrication of Pd nanowires was controlled by analyzing the current–time transient during electrodeposition using potentiostat. The AAO template and the Pd nanowires were characterized by scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) methods and X-Ray diffraction (XRD). It was observed that the Pd nanowire array was standing freely on an Au-coated Ti substrate after removing the AAO template in a relatively large area of about 5 cm(2), approximately 50 nm in diameter and 2.5 μm in length with a high aspect ratio. The nucleation rate and the number of atoms in the critical nucleus were determined from the analysis of current transients. Pd nuclei density was calculated as 3.55 × 10(8) cm(−2). Usage of diluted neutral electrolyte enables slower growing of Pd nanowires owing to increase in the electrodeposition potential and thus obtained Pd nanowires have higher crystallinity with lower dislocations. In fact, this high crystallinity of Pd nanowires provides them positive effect for sensor performances especially.